Hypertrophic remodelling of retinal arterioles in patients with congestive heart failure - Jung, Susanne; Kolwelter, Julie; Bosch, Agnes; Cífková, Renata; Harazny, Joanna M.; Ott, Christian; Achenbach, Stephan; Schmieder, Roland (ESC Heart Failure, 2021)
Aims: Analysis of microvascular parameters in the retinal circulation—known to reflect those in the systemic circulation—allows us to differentiate between eutrophic and hypertrophic remodelling of small arteries. This study aimed to examine microvascular changes in patients with congestive heart failure (CHF) and reduced as well as mid-range ejection fraction. Methods and results: Forty subjects with CHF underwent measurement of retinal capillary flow (RCF), wall-to-lumen ratio (WLR), vessel and lumen diameter, wall thickness, and wall cross-sectional area (WCSA) of retinal arterioles of the right eye by scanning laser Doppler flowmetry (SLDF). Applying a matched pair approach, we compared this group with reference values of age-matched controls from a random sample in the population of Pilsen, Czech Republic. There was no significant difference in RCF and WLR between the groups (RCF: P = 0.513; WLR: P = 0.106). In contrast, wall thickness and WCSA, indicators of hypertrophic remodelling, were higher in CHF subjects (WT: 15.0 ± 4.2 vs. 12.7 ± 4.2 μm, P = 0.021; WCSA: 4437.6 ± 1314.5 vs. 3615.9 ± 1567.8 μm2, P = 0.014). Similarly, vessel (109.4 ± 11.1 vs. 100.5 ± 14.4 μm, P = 0.002) and lumen diameter (79.0 ± 7.9 vs. 75.2 ± 8.5 μm, P = 0.009) were increased in CHF. Conclusions: In CHF subjects, we observed hypertrophic remodelling of retinal arterioles indicative of similar changes of small resistance arteries in the systemic circulation. Microvascular structure and function assessed by SLDF may thereby represent a useful, non-invasive method for monitoring of microvascular damage in patients with CHF and may offer innovative treatment targets for new CHF therapies.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Heart failure; Hypertrophic remodelling; Microvasculature; Retina